2021
DOI: 10.3390/en14248266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Burner Wall Material on Microjet Hydrogen Diffusion Flames near Extinction: A Numerical Study

Abstract: Characteristics of microjet hydrogen diffusion flames stabilized near extinction are investigated numerically. Two-dimensional simulations are carried out using a detailed reaction mechanism. The effect of burner wall material, thickness, and thermal radiation on flame characteristics such as flame height and maximum flame temperature are studied. Results show that the flame stabilizes at lower fuel jet velocities for quartz burner than steel or aluminum. Higher flame temperatures are observed for low conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Additionally, the flame stability was greatly improved and the flammable range of the combustor was enlarged. Muraleedharan et al [24] numerically investigated the effect of wall material and thickness on flame height and flame temperature for micro-jet flames with hydrogen as fuel. It was found that when the burner conductivity was low, flame temperature was high, whereas flame length increased with thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the flame stability was greatly improved and the flammable range of the combustor was enlarged. Muraleedharan et al [24] numerically investigated the effect of wall material and thickness on flame height and flame temperature for micro-jet flames with hydrogen as fuel. It was found that when the burner conductivity was low, flame temperature was high, whereas flame length increased with thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The length of the flame increases with the increasing thermal conductivity of the burner wall. From a practical point of view, a quartz burner may be the optimal solution for micro-diffusion flame applications with lower fuel flow rates [16].…”
Section: Introductionmentioning
confidence: 99%